ESTIMASI KANDUNGAN AIR PADA TUMBUHAN PADI MENGGUNAKAN MODIS SINTETIK - Michael Michael (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
Remote sensing is a technology that is used to gather all the information from the Earth without touching the object directly. In this case, precision farming used remote sensing to make better result for rice field agriculture. The aim of this research is to predict the water content. The prediction of water content result can be used for monitoring the condition of the paddy. In this research, the data training is from ground based spectrometer in Karawang, West Java with 4 bands, e.g. band 1, band 2, band 3, band 4. MODIS satellite of Karawang , West Java is used for testing. There are two steps in doing the experiment, training and testing. For the training, we use Modified Bootstrap Regression and Modified Robust Tukey Regression. For testing, we use the ordinary mutilinear regression to estimate the water content in the paddy. Modified Bootstrap Regression is not as good as Modified Robust Tukey Regression, because in training process, it needs longer time than Modified Robust Tukey Regression. For the evaluation, the testing data is the training data from ground based. Modified Bootstrap Regression and Modified Robust Regression got 34.44% as the highest. Key wordsRemote Sensing, Crop Estimation, Precision Farming, MODIS, Ground based, Modified Bootstrap Regression, Modified Robust Tukey Regression